Analisis Kualitas Website Perpustakaan Universitas Islam Negeri Sumatera Utara (UINSU) dengan Menggunakan Metode Webqual 4.0 - Yanti, Rizki Febri; Sayekti, Retno; Fathurrahman, Muslih (Comit: Communication, Information and Technology Journal, 2024)
This research aims to measure the service quality of the North Sumatra Islamic State University Library UPT website by comparing the level of performance and level of interest (expectations) of users. The research method uses the webqual 4.0 method with three main variables: Usability, Information Quality, and Service Interaction Quality. The research sample involved 98 respondents with data collection using a questionnaire. Data analysis was carried out using descriptive statistical analysis and simple linear regression, with the help of SPSS Version 23 software. Hypothesis test results show that there is a positive and significant influence between performance variables and website importance, with tcount > ttable (4.998 > 0.16608) and level significance 0.000 (below 0.05). Therefore, the conclusion drawn is that Ho is rejected and Ha is accepted, indicating that there is a positive and significant influence between variables X and Y.